HUBUNGAN PENDIDIKAN DAN USIA IBU DENGAN KELENGKAPAN IMUNISASI TETANUS TOXOID (TT) PADA IBU HAMIL DI PUSKESMAS SEKIP PALEMBANG - Ike Sri Wahyuni; Riska Widya Astuti; Bulan Purnama Sari (Rena Cipta Mandiri, 2025)
Immunization against Tetanus Toxoid (TT) is a preventive measure to increase immunity against tetanus infections, specifically to prevent neonatal tetanus and reduce maternal and infant mortality. However, pregnant women often underutilize available healthcare services, one of which is the low coverage of TT immunization. The purpose of this study was to determine the factors influencing the completeness of TT immunization in pregnant women. This analytical research used a cross-sectional study approach and accidental sampling technique. The study population included all pregnant women who visited healthcare facilities for check-ups, with 48 respondents as the sample. The results showed that a significant number of respondents did not receive complete TT immunization. Most of the respondents had low education levels (29 respondents, 60.4%) and were at high-risk ages (30 respondents, 62.5%). The Chi-square statistical test revealed that the independent variables, education (p = 0.041) and age (p = 0.016), significantly affected TT immunization completeness (p-value < α = 0.05). Efforts to increase TT immunization coverage should focus on mothers with low education and those in high-risk age groups. It is recommended that pregnant women receive complete TT immunization to prevent neonatal tetanus and maternal tetanus infections.